A REFUTATION FROM CAPITALISM TOWARD ENVIRONMENTALISM’S CRITICS RELATED ENVIRONMENTAL PROBLEM - Farucha, Riska Fara; Asnawi, Naupal (International Review of Humanities Studies, 2021)
From environmentalism’s perspective, there are four fundamental assumptions that make capitalism inconsistent with efforts to preserve the environment. First, unlimited growth in the capitalist system is contradicted with limited environmental conditions. Second, the basic principles of capitalism (individual freedom, self-interests, and free-market) are not compatible with efforts to preserve the environment. Third, capitalism has caused a "metabolic rift" between society and the ecosystem. Fourth, the tendency of capitalism that creates consumer society will produce massive pollution. This article is intended to refute these four environmentalism critics and also demonstrate the coherence of the theory of capitalism on environmental preservation. To accomplish this aim, the method of refutation is first used to show the shortcomings of the claim about environmentalism in its critique, then continue with an analytical explanation of the whole theory of capitalism, and conclude with a theoretical elaboration of all these concepts. This paper argues that environmentalism critics are irrelevant because capitalism is actually capable of preserving the environment.